Strengthening Capital Markets : National Progress and Gaps - Cuervo, Cristina; Long, Jennifer; Stobo, Richard.. (Washington, D.C. : International Monetary Fund, 2022)
This paper discusses progress on post-global financial crisis (GFC) reforms and the emerging challenges in the area of capital markets regulation and supervision, drawing on the analysis and insights from the IMF's Financial Sector Assessment Program (FSAP). FSAP analyses sheds light on the implementation of post-GFC reforms to strengthen prudential and conduct supervision of capital markets and highlights new regulatory and supervisory challenges arising from several factors such as the growth of bond markets, benchmark transition, digitalization, and climate change. Key takeaways regarding implementation of post-GFC reform include significant progress with respect to oversight of market intermediaries and infrastructures and a case for further regulatory and supervisory action to address vulnerabilities arising from the high and rising interconnectedness of the asset management sector with the global economy, especially to foster stronger liquidity risk management. Emerging priority areas underscore the importance of ensuring the adequacy of issuer disclosures and quality of auditing; of examining and appropriately calibrating the regulatory perimeter in light of market developments; and of proactively safeguarding the operational independence of supervisory authorities and adequacy of their resources for implementation of regulatory frameworks that are fit-for-purpose in light of market developments and evolution.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Non-Bank Financial Institutions; Pension Funds; Political Economy